Cellular Automata Simulations of Thermal Transport Properties of Thin-Film Polymer/CNTs Nano-Composites for Improved Design. Issue 1619 (28th July 2014) - Kalakonda, P.; Casey, A.; Iannacchione, G. S.; Georgiev, G. Y.; Cabrera, Y.; Judith, R.; Cebe, P.
ABSTRACT A computational algorithm has been developed to simulate the transport properties of oriented and un-oriented thin film nanocomposites of isotactic Polypropylene (iPP) and carbon nanotubes (CNT) with increasing CNT concentration. Our goal is to be able to design materials with optimal properties using these simulations. We use a cellular automata approach in a Matlab 3-D array environment. The percolation threshold is reproduced in the simulations, matching experimental data. Upon percolation, the thermal transport in the films increases sharply, due to the large difference in the thermal conductivities of the CNTs and the polymer. To verify the simulation, the thin-film samples were sheared in the melt at 200C at 1 Hz in a Linkan microscope shearing hot stage. The thermal conductivity measurements were performed on the same cell arrangement with the transport perpendicular to the thin-film plane using a DC method. The thermal conductivity is higher for the un-sheared as compared to the sheared samples. Our cellular automata simulations provide information about the microstructuremacroscopic property relation in the thin film nanocomposites and can be extended to simulations of other important materials.